2009
DOI: 10.1089/jop.2009.0005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Topical Application of Timolol and Verapamil in Patients With Glaucoma Within 6 Months

Abstract: It seems that topical verapamil has a similar effect to timolol in patients with open-angle glaucoma, so it can be considered as a lowering intraocular pressure agent in glaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Of note, this NMDA‐model is a chemically induced RGC death model and does not induce increases in IOP. Interestingly, while chronic topical administration of verapamil can reduce IOP, systemic treatment with verapamil has little effect in lowering IOP (Liu et al ., 1996; Mikheytseva et al ., 2004; Shayegan et al ., 2009). Here, we have demonstrated the systemic neuroprotective effects of verapamil via inhibiting TXNIP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this NMDA‐model is a chemically induced RGC death model and does not induce increases in IOP. Interestingly, while chronic topical administration of verapamil can reduce IOP, systemic treatment with verapamil has little effect in lowering IOP (Liu et al ., 1996; Mikheytseva et al ., 2004; Shayegan et al ., 2009). Here, we have demonstrated the systemic neuroprotective effects of verapamil via inhibiting TXNIP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium channel blockers may also inhibit the synthesis of extracellular matrix collagen protein, suggesting beneficial effect in glaucoma. 13 CCBs cause relaxation of trabecular mesh work cells by inhibition of L-type channels which increases outfow facility of aqueous humor. The perfusion studies in dissected human eyes showed dose-related increase in outfow facility after verapamil administration.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] In this proof of principle study, we did not intend to determine the amount of microbeads required to achieve, for example, a reduction of IOP by 5 mmHg since the pharmacokinetics of timolol differ between humans and rabbits. Indeed, previous studies have demonstrated that timolol is less effective in rabbits than humans, [33][34][35][36][37] suggesting that the use of timolol spheres may have a more marked effect in humans, and particularly in eyes with elevated IOP. Our data do demonstrate that sustained delivery of timolol is possible using this vehicle.…”
Section: Discussionmentioning
confidence: 99%